2012
DOI: 10.3109/09546634.2012.672710
|View full text |Cite
|
Sign up to set email alerts
|

Investigator-initiated, open-label trial of ustekinumab for the treatment of moderate-to-severe palmoplantar psoriasis

Abstract: This study demonstrates that ustekinumab dosed at 90 mg is effective in controlling signs and symptoms of palmoplantar psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 53 publications
1
70
2
1
Order By: Relevance
“…The SD for changes in DLQI scores is approximately 7 units; 16 thus, if 80% of the 210 patients scheduled for enrollment ( n  =   167) were evaluable for the analysis of change in DLQI scores from baseline, then the distance from the boundaries of the two‐sided 95% confidence interval (CI) to the point estimate would be 1.07 units.…”
Section: Methodsmentioning
confidence: 99%
“…The SD for changes in DLQI scores is approximately 7 units; 16 thus, if 80% of the 210 patients scheduled for enrollment ( n  =   167) were evaluable for the analysis of change in DLQI scores from baseline, then the distance from the boundaries of the two‐sided 95% confidence interval (CI) to the point estimate would be 1.07 units.…”
Section: Methodsmentioning
confidence: 99%
“…So war in einer Studie gegenüber Placebo kein Vorteil zu sehen [65]. In einer anderen Studie zeigten sich dagegen bei einer Dosis von 90 mg bessere Erfolge [68]. [74]).…”
Section: Introductionunclassified
“…Au and colleagues studied the role of UST in 20 subjects with moderate-to-severe psoriasis of the palms and soles [Au et al 2013]. They treated patients who have previously failed topical steroids with UST at weeks 0, 4 and 16.…”
Section: Efficacymentioning
confidence: 99%
“…At 24 weeks, mean values showed 56% improvement in Dermatology Life Quality Index, and 34% improvement in pain Visual Analogue Scale score (all p < 0.05). It was concluded that UST dosed at 90 mg is effective in controlling signs and symptoms of palmoplantar psoriasis [Au et al 2013]. …”
Section: Efficacymentioning
confidence: 99%